Assessing the diversity of sea beet (Beta vulgaris L. ssp. maritima) populations - Ascarini, F. (2022)
Beta vulgaris L. subsp. maritima (L.) Arcang., sea beet, is a morphologically and genetically variable species, belonging to beet primary gene -pool. This crop wild relative is a valuable genetic resource for resistance improvement in beets and could play an important role in crop yield sustainability. Eleven Madeiran sea beet populations were characterized using morphological descriptors and genetic markers. Our goal was to evaluate these populations as a potential source of valuable genetic material. Morphological characterization showed a high quantitative variation among populations. Plant height and inflorescence height parameters had the highest influence in the separation of populations. Molecular analysis was performed with polymorphic SSRs to determine genetic variability between populations. Both PCA and PCoA revealed three clusters that separated the populations according to morphological and genetic traits, respectively. This study contributes to the knowledge of sea beet diversity in Madeira’s archipelago and to the perception that the islands' specific environmental conditions influence its genetic variability, making these populations a possible gene source for sugar beet breeding programs